Patients providing the answers: narrowing the gap in data quality for emergency care. Issue 5 (27th May 2010) - Porter, Stephen C; Forbes, Peter; Manzi, Shannon; Kalish, Leslie A
Abstract : Objective: The authors examined the validity of documentation produced during paediatric emergency care to determine if a patient-driven health information technology called ParentLink produced higher-quality data than documentation completed by nurses and physicians. Design: The authors analysed the quality of information across elements of allergies to medications and the history of present illness (HPI) collected during a quasi-experimental intervention study where control periods with usual care alternated with intervention periods when ParentLink was operational. Documentation by emergency department (ED) providers was abstracted and compared with information generated through ParentLink . The criterion standard for the history of allergies to medications was a structured telephone interview with parents after the ED visit. A valid report for a medication allergy was one that was both accurate and complete. Completeness of the HPI for acute head trauma was evaluated across seven elements relevant to an evidence-based risk assessment. Results: Of 1410 enrolled parents, 1111/1410 (79%) completed the criterion standard interview. Parents' valid reports of allergies to medications were higher than those of nurses (parents 94%, nurses 88%, p<0.0001). Parents' valid reports of allergies to medications were greater than those of physicians (parent 94%, physicians 83%, p<0.0001). ParentLink produced more complete information on HPI for head trauma than the medical record for five of seven elements. Conclusion: ParentLink provided electronic information that met or exceeded the quality of data documented by ED nurses and physicians.